PERAN CELEBRITY ENDORSER DALAM MEMPERKUAT PENGARUH PERCEIVED VALUE TERHADAP PURCHASE INTENTION - Retno Susanti & Suprihatmi Sri Wardiningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
This research aimed to analyze the influence of consumer perceptions, price perception and perceived risk to the success of private label brands in the retail company Carrefour in Solo. Primary data obtained from questionnaires to 100 respondents using purposive sampling techniques, and performed analyzes with SPSS version 12.0, with the results all questionnaire are valid and reliable. Analysis multiple linear regression, F-test, t-test, and the coefficient determination, with the result: Consumer Perceptions (X1), Price Perception (X2), and the Perceived Risk (X3) significantly influencing the success of private label brands, and price perception variable is a dominant variable on the success of private label brands. It means the data obtained supports the hypothesis. Research found that the quality of the product is perceived by consumers, they believe that private label brands with low prices image have quality that is comparable to the national brands, consumers are not ashamed and do not have to bear the risk of purchasing the products. These all are the factors that are proven to be the perception in purchasing private label products brands. Keywords: Consumer Perceptions, Price Perception, Perceived Risk, Private Label Brand.